2020
DOI: 10.1186/s40703-020-00111-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on the bearing capacity of encased stone columns

Abstract: Stone columns have attracted considerable attention as a ground improvement techniques recently. Performance of stone columns, however, depends on confining pressure offered by the surrounding soils. In the case of very soft soils, the lateral confining pressure may be insufficient and this may lead to column bulging failure. Encapsulating the individual stone column enhances the lateral resistance against bulging by additional confining pressure. In this study, the influences of the length of encasement and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The geotechnical engineering program, Finite Element Package (Plaxis 2D V21), was used to analyze the behavior of an embankment on soft soil. Several researchers have extensively used it to analyze various geotechnical problems (Rajesh and Jain, 2015;Lo et al, 2010;Hataf et al, 2020). As stated in Tab.…”
Section: Validation Of the Modelmentioning
confidence: 99%
“…The geotechnical engineering program, Finite Element Package (Plaxis 2D V21), was used to analyze the behavior of an embankment on soft soil. Several researchers have extensively used it to analyze various geotechnical problems (Rajesh and Jain, 2015;Lo et al, 2010;Hataf et al, 2020). As stated in Tab.…”
Section: Validation Of the Modelmentioning
confidence: 99%
“…As a result, the stone column bulges and pushes the surrounding soil radially, reducing efficiency. Hence, studies have tried to employ various geosynthetics to reinforce the stone column and provide confining pressure around it [6][7][8][9][10][11][12], and reduce stress concentration at the column's top by placing a reinforced granular blanket [13,14]. In response to this improvement, the stone column can take vertical loads and reduce bulging.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers found that encapsulating the upper portion of a stone column at 2.5 D (D) the pillar's diameter has demonstrated its usefulness in this field, resulting in a precipitation reduction of up https://doi.org/10.17993/3ctecno.2023.v12n2e44.78-91 to 50%. (18,19). The encasement, which has several advantages, further restrains the stone column.…”
Section: Introductionmentioning
confidence: 99%